Factors affecting hypertension among the Malaysian elderly - Eshkoor, Sima Ataollahi; Tengku Abdul Hamid, Tengku Aizan; Shahar, Suzana; Ng, Chee Kyun; Chan, Yoke Mun (MDPI, 2016)
Hypertension is a common chronic disease in the elderly. This study aimed to determine the effects of age, ethnicity, gender, education, marital status, nutritional parameters, and blood elements on the risk of high blood pressure in the Malaysian elderly. This research was conducted on a group of 2322 non-institutionalized Malaysian elderly. The hierarchy binary logistic regression analysis was applied to estimate the risk of hypertension in respondents. Approximately, 45.61% of subjects had hypertension. The findings indicated that the female gender (Odds ratio (OR) = 1.54), an increase in body weight (OR = 1.61), and an increase in the blood levels of albumin (OR = 1.51), glucose (OR = 1.92), and triglycerides (OR = 1.27) significantly increased the risk of hypertension in subjects (p < 0.05). Conversely, an increase in both dietary carbohydrates (OR = 0.74), and blood cholesterol level (OR = 0.42) significantly reduced the risk of hypertension in samples (p < 0.05). Furthermore, the results showed that ethnicity was a non-relevant factor to increase the risk of hypertension in subjects. It was concluded that female gender, an increase in body weight, and an increase in the blood levels of glucose, triglycerides, and albumin enhanced the risk of high blood pressure in the Malaysian elderly. In addition, an increase in both dietary carbohydrates and blood cholesterol level decreased hypertension in subjects.